Techno-economic and Environmental Assessment of a Biorefinery for the Valorisation of Sesame Crop - Juan M. Gonzalez; Angie Y. Salazar; Yeny Portela; Eduardo L. Sanchez; Karina A. Ojeda (Chemical Engineering Transactions)
Sesame (Sesamum indicum L) is an oilseed cultivated in tropical regions of Asia, Africa, and South America and is traditionally used in Asian cuisine as cooking oil. Thanks to its adaptability to poor soils and relatively high-temperature conditions, its high oil content (approximately 60%), and its antioxidant properties, sesame is a valuable commodity for the industrial production of food, cosmetics, pharmaceuticals, polymers, and fuels. In this study, a sesame-based biorefinery is proposed to produce food products (refined cooking oil and a vegetable milk substitute), chemical reagents (epoxide sesame oil resin), and fuels (biodiesel and bioethanol) through the esterification of sesame oil and the modification-fermentation of residual sesame crop biomass, respectively. The feasibility of the biorefinery was assessed using life cycle assessment and techno-economic evaluations. Both economic and environmental analysis indicate that all technological pathways are viable for implementation. The results suggest that the production of food-based products offers a faster return on investment and lower environmental impact. However, a combined production strategy incorporating epoxide resin and biodiesel may be considered, depending on market demand.